2018
DOI: 10.1155/2018/7104352
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Procalcitonin, Interleukin-6, and Fibrinogen Levels in Differential Diagnosis of Diabetic Foot Ulcer Infection

Abstract: Aims We aimed to evaluate the roles of interleukin-6 (IL-6), PCT, and fibrinogen levels in the differential diagnosis of the patients with infected diabetic foot ulcer (IDFU) and noninfected diabetic foot ulcer (NIDFU) and to compare those with C-reactive protein (CRP), white blood cell (WBC), and erythrocyte sedimentation rate (ESR). Methods Patients over 18 years with a diagnosis of type 2 diabetes mellitus and DFU who were followed up in our hospital between 1 January 2016 and 1 January 2017 were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 25 publications
2
43
0
1
Order By: Relevance
“…About half of the studies we included investigated the value of the WBC for assessing infection of a DFU, and these generally found no significant correlation between the WBC counts and the infection severity . All but two studies of serum PCT values reported that they were significantly higher in infected than noninfected DFU; in one other study, PCT was found significantly higher in patients with osteomyelitis . No published study has reported a correlation between the level of PCT and the severity of infection according to the IDSA/IWGDF classification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…About half of the studies we included investigated the value of the WBC for assessing infection of a DFU, and these generally found no significant correlation between the WBC counts and the infection severity . All but two studies of serum PCT values reported that they were significantly higher in infected than noninfected DFU; in one other study, PCT was found significantly higher in patients with osteomyelitis . No published study has reported a correlation between the level of PCT and the severity of infection according to the IDSA/IWGDF classification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the role of various inflammatory biomarkers measured in blood for diagnosing infection and in distinguishing skin/soft tissue infection from osteomyelitis in diabetic patients with a foot ulcer . Most of the published studies have addressed the value of WBC, ESR, CRP, or PCT by comparing serum levels with the presence of clinical signs of infection . About half of the studies we included investigated the value of the WBC for assessing infection of a DFU, and these generally found no significant correlation between the WBC counts and the infection severity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular note is the WBC level, as it is used as part of the IDSA/IWGDF criteria for classifying infection as severe/grade 4. The available studies found little correlation with infection severity, with about half of the patients diagnosed with a DFI having a normal WBC . In most studies, ESR values have been higher in patients with an IDFU compared with a noninfected DFU (NIDU) .…”
Section: Diagnosismentioning
confidence: 99%